Executive functions in children with communication impairments, in relation to autistic symptomatology. 1: generativity - Bishop, D; Norbury, C (SAGE Publications, 2005)
Previous research has found that people with autism generate few novel responses in ideational fluency tasks, and it has been suggested this deficit is a specific correlate of sterotyped/repetitive behavior. We assessed generativity in children with pragmatic language impairment (PLI) who showed communicative abnormalities resembling those seen in autism. We compared four groups: high-functioning autism; PLI; specific language impairment; and control. Generativity was measured using two fluency tasks previously shown to be sensitive to autistic disorder. Correlational analysis revealed a significant relationship between the percentage of correct responses on the fluency tasks and measures of communicative abnormality. It is often assumed that pragmatic difficulties are caused by limitations of social cognition. This study suggests that difficulties in generating relevant ideas can be another cause of autistic-like communicative abnormalities.